Aprendizado baseado em problemas (problem based learning): a sua importância no ensino da contabilidade - Oliveira, Evaneide Barbosa de (2010)
The objective of this work is the implementation of a study that allows the analysis of the Problem-based learning (PBL) methodology, to clearly identify the possible contributions to the teaching learning process of Accounting. This study is characterized by the Exploratory Search design to achieves deeply the knowledge of the Problem-based learning (PBL) in such way that can take it as a contribution source to the Accounting Science learning. At the same time, this study is based on the methodological approach in the qualitative research, where explores the observation and interviewing techniques in order to establish both analysis the content analysis and the historical strategy analysis. This study also has some quantitative analysis method that will gather quantitative data of a specific population, using a closed question table as a sample of analysis and interpretation and measurement proceeds to this study. This study observed and highlights that the Problem-based learning (PBL) can be introduced into the Accountancy course, respecting the existent literary framework that is strongly important for this tool application success, such as the limits of the acceptability, responsibility, commitment and adequacy to meet the demand generated: the ability of solving problems, and also the need of a teaching methodologies renewal in a way that the student could develop his critical thought, logical reasoning, the introduction to the research, the teamwork, the interpersonal relationship and the conflict resolution skills. This study was made to contribute to the search topic of the Accounting Theory Program Graduate strictu sensu of PUC-SP in Accountancy and Actuarials